Ativismo de mulheres cristãs: enfrentamentos e afinidades - Jorge, Simone Aparecida (2021)
Contemporary societies have observed an amplification of the reach of the Internet and social networks as instruments of political organization, and digital activism has acquired protagonism in several localities of the world. As a result of this context, cyberspace has become an enabling environment for the organization of thousands of people, mobilization and engagement in the imminent political debate. The object of study addressed in this research was composed of organized groups of Christian women who use the Internet and social networks for political activism and the expression of their ideological positions. The Internet and social networks were researched as channels that propagate ideas and debates about issues that are costly to feminist movements and that, diametrically, mobilize conservative segments. The proposed objectives were to identify how organized and antagonistic groups of Christian women approach issues such as the decriminalization of abortion, guarantee of sexual and reproductive rights, prevention of violence against women, among others, and how the virtual public reacts to these positions. The research has chosen virtual ethnography as the method and technique of research, and in-depth interviews with representatives of the different segments observed. It carried out an analysis of a possible alliance between the progressive movements of society and the "Féministas", groups of religious activists who do not admit Christian dogmas when they overlap with individual rights. The groups of conservative Christian women, investigated in this study, showed their defenses of a profile of a woman who must be obedient to God and her husband, always in conformity with the social roles imposed. The activism of religious women concomitantly witnessed the formulation of a theoretical reference, called Feminist Theology, original for presenting an innovative narrative based on the deconstruction of ancient and solidified religious discourses that historically impose on women and LGBTQI+ people a subaltern place and, in many situations, of concealment. Feminist theology is inclusive, affective and welcomes people who suffer injustice and discrimination